Two-dimensional nanomaterials for sensing applications - Huang, Ying (2018)
Two-dimensional (2D) nanomaterials have recently received increasing research interest because of their intriguing structures and properties. Particularly, 2D metal-organic framework (MOF) and covalent-organic framework (COF) nanosheets are emerging members in the 2D family. The ability to prepare 2D MOF and COF nanosheets is paramount to study their unique properties and potential applications. However, it is still in its infancy. Therefore, my thesis aims to prepare novel ultrathin 2D MOF and COF nanosheet as well as 2D MOF-based composite nanosheets and explore their properties and potential applications in sensors. To this end, the following work has been done. First, a series of 2D metalloporphyrinic MOF (Cu-TCPP(M), TCPP=tetrakis(4-carboxyphenyl)porphyrin, M=Fe, Co, and Mn) nanosheets with thickness of sub-10 nm were prepared by surfactant-assisted synthetic method, where metalloporphyrins (TCPP(Fe), TCPP(Co), and TCPP(Mn)) were used as ligands and Cu paddle-wheel units were employed as nodes. The obtained 2D MOF nanosheets could act as artificial enzyme, exhibiting excellent peroxidase-like activity. In light of this, Cu-TCPP(Fe) nanosheets were developed as the sensing platform to fabricate colorimetric sensor for the sensitive detection of glucose in serum samples. Second, 2D MOF-based composite nanosheets (Au NP/Cu-TCPP(Fe) and Au NP/Cu-TCPP(Co)) were prepared by using 2D Cu-TCPP(Fe) and Cu-TCPP(Co) nanosheets as templates, where Au NPs with small size were grown. Since the obtained Au NP/Cu-TCPP(Fe) and Au NP/Cu-TCPP(Co) composite nanosheets had the peroxidase-like activity and glucose oxidase-like activity, they were utilized for mimicking nature multi-enzyme system, achieving the artificial enzyme cascade reaction. Furthermore, Au NP/Cu-TCPP(Fe) composite nanosheets were used as the sensing platform to construct colorimetric sensor for biomolecular detection. Last, novel 2D imine-linked COF (TPA-COF) nanosheets were prepared by selecting two flexible building units with C3v molecular symmetry. The obtained bulk TPA-COF with a hexagonal layered structure and sheet-like morphology was easily exfoliated into ultrathin 2D TPA-COF nanosheets, as the bulk TPA-COF has the weak interlayer π-π stacking interaction. The pore channels and individual building units of TPA-COF nanosheet were visualized by using low-dose TEM technique. Moreover, the exfoliated TPA-COF nanosheets were applied as the efficient fluorescence sensing platform for sensitive and selective detection of DNA.